Penentuan Rute Angkutan Tandan Buah Segar (TBS) Kelapa Sawit Yang Optimal dengan Metode Saving Matrix - M Hudori; Sylvia Madusari (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
This research aims to determine the optimal transportation of fresh fruit bunches (FFB) of palm oil using the Saving Matrix. The first step in the use of Saving Matrix method is to identify the distance matrix between palm oil mill (POM) with a main assembly point of bunch harvested (TPH) in division and the distance between each main TPH. A savings from two different routes that can be calculated after an unknown distance matrix. Based on the saving matrix then the next step is to consolidate the load, which allocates the load of main TPH to the vehicle and route. Allocation or merger is done with the greatest distance maximize saving by considering the capacity of the vehicle. The next step is to sort these visits to get the shortest travel distance that can be reached. The results of this study indicate that the use of saving matrix method in determining the transportation route for TBS can provide significant saving in each week.